Ex Post Information Rents in Sequential Screening - Daniel Krähmer; Roland Strausz (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study ex post information rents in sequential screening models where the agent receives private ex ante and ex post information. The principal has to pay ex post information rents for preventing the agent to coordinate lies about his ex ante and ex post information. When the agent's ex ante information is discrete, these rents are positive, whereas they are zero in continuous models. Consequently, full disclosure of ex post information is generally suboptimal. Optimal disclosure rules trade off the benefits from adapting the allocation to better information against the effect that more information aggravates truth-telling.
Keywords: D82; H57; 330; information rents; sequential screening; information disclosure